Epigenetics and Malaria Susceptibility/Protection: A Missing Piece of the Puzzle - Arama, Charles; Quin, Jaclyn E.; Kouriba, Bourèma; Östlund Farrants, Ann-Kristin; Troye-Blomberg, Marita; Doumbo, Ogobara K. (Frontiers in Immunology, 2018)
A better understanding of stable changes in regulation of gene expression that result from epigenetic events is of great relevance in the development of strategies to prevent and treat infectious diseases. Histone modification and DNA methylation are key epigenetic mechanisms that can be regarded as marks which ensure an accurate transmission of the chromatin states and gene expression profiles over generations of cells. There is an increasing list of these modifications and the complexity of their action is just beginning to be understood. It is clear that the epigenetic landscape plays a fundamental role in most biological processes that involve the manipulation and expression of DNA. Although the molecular mechanism of gene regulation is relatively well understood, the hierarchical order of events and dependencies that lead to protection against infection remain largely unknown. In this review, we propose that host epigenetics is an essential, though relatively under studied, factor in the protection or susceptibility to malaria.